Savage grace - Robins, Natalie (Morrow, 1985)
Drawing on private diaries, confidential documents, and interviews, the authors relate the tragic ordeal of the Baekelands, a jet set family torn apart by love triangles, incest, matriclde, black magic, drugs and suicide. A spellbinding tale of money and madness, incest and matricide, Savage Grace is the saga of Brooks and Barbara Baekeland -- beautiful, rich, worldly -- and their handsome, gentle son, Tony. Alternately neglected and smothered by his parents, he was finally driven to destroy the whole family in a violent chain of events. Savage Grace unfolds against a glamorous international background (New York, London, Paris, Italy, Spain); features a nonpareil cast of characters (including Salvador Dalí, James Jones, the Astors, the Vanderbilts, and European nobility); and tells the doomed Baekelands' story through remarkably candid interviews, private letters, and diaries, not to mention confidential hospital, State Department, and prison documents. A true-crime classic, it exposes the envied lives of the rich and beautiful, and brilliantly illuminates the darkest corners of the American Dream.